A methodology for microstructure-based structural optimization of cast and injection moulded parts using knowledge-based design automation. (July 2017) - Olofsson, Jakob; Salomonsson, Kent; Johansson, Joel; Amouzgar, Kaveh
Highlights: A new methodology for geometry optimization with consideration of heterogeneous material behaviour is presented. Mechanical behaviour is based on local microstructure formation predicted by simulations and microstructure models. Design automation and a multi-objective optimization algorithm is used for controlling the knowledge-based implementation. The approach is implemented for cast materials and injection moulded glass-fibre reinforced polymeric materials. Abstract: The local material behaviour of cast metal and injection moulded parts is highly related to the geometrical design of the part as well as to a large number of process parameters. In order to use structural optimization methods to find the geometry that gives the best possible performance, both the geometry and the effect of the production process on the local material behaviour thus has to be considered. In this work, a multidisciplinary methodology to consider local microstructure-based material behaviour in optimizations of the design of engineering structures is presented. By adopting a knowledge-based industrial product realisation perspective combined with a previously presented simulation strategy for microstructure-based material behaviour in Finite Element Analyses (FEA), the methodology integrates Computer Aided Design (CAD), casting and injection moulding simulations, FEA, design automation and a multi-objective optimization scheme into a novel structural optimization method for cast metal and injection moulded polymeric parts. The different concepts and modules in the methodology are described, their implementation into a prototype software is outlined, and the application and relevance of the methodology is discussed.